Beyond immortality: Epstein–Barr virus and the intricate dance of programmed cell death in cancer development - Arezoo Esmaeili; Prankur Awasthi; Samira Tabaee (Cancer Treatment and Research Communications)
This comprehensive review delves into the intricate role of programmed cell death in Epstein–Barr virus (EBV)-associated malignancies, focusing on the sophisticated interplay between viral mechanisms and the host's immune response. The central objective is to unravel how EBV exerts control over cell death pathways such as apoptosis, ferroptosis, and autophagy, thereby fostering its persistence and oncogenic potential. By dissecting these mechanisms, the review seeks to identify therapeutic strategies that could disrupt EBV's manipulation of these pathways, enhancing immune recognition and opening new avenues for targeted treatment. A deeper understanding of the molecular underpinnings of EBV's influence on cell death not only enriches the field of viral oncology but also pinpoints targets for drug development. Furthermore, the insights gleaned from this review could catalyze the design of vaccines aimed at preventing EBV infection or curtailing its oncogenic impact. Innovatively, the review synthesizes recent discoveries on the multifaceted roles of non-coding RNAs and cellular signaling pathways in modulating cell death within the context of EBV infection. By consolidating current knowledge and identifying areas where understanding is lacking, it lays the groundwork for future research that could lead to significant advancements in vaccine development and therapeutic interventions for EBV-related cancers. This review underscores the critical necessity for ongoing investigation into the complex interplay between EBV and host cell death mechanisms, with the ultimate goal of enhancing patient outcomes in EBV-associated diseases.